Walking Along Curved Trajectories. Changes With Age and Parkinson's Disease. Hints to Rehabilitation - Godi, Marco; Giardini, Marica; Schieppati, Marco (Frontiers in Neurology, 2019)
We briefly recall the fundamental processes allowing us to change locomotion trajectory and keep walking along a curved path and provide a review of contemporary literature on turning in older adults and people with Parkinson’s Disease (PD). The first part briefly summarizes the way the body exploits the physical laws for producing a curved walking trajectory. Then, the changes in muscle and brain activation underpinning this task, and the promoting role of proprioception, are briefly considered. Another section is devoted to the gait changes occurring in curved walking and steering with ageing. Further, freezing during turning and rehabilitation of curved walking in patients with PD is mentioned in the last part. Obviously, the research on body steering while walking or turning has boomed in the last ten years, the relevant critical issues have been tackled and ways to improve this locomotor task proposed. Rationale and evidences for successful training procedures are available, potentially able to reduce the risk of falling in both older adults and patients with PD. A better understanding of the pathophysiology of steering, of the subtle but vital interaction between posture, balance and progression along non-linear trajectories, and of the residual motor learning capacities in these cohorts may provide solid bases for new rehabilitative approaches.